2017
DOI: 10.18632/oncotarget.16584
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced tumor growth inhibition by mesenchymal stem cells derived from iPSCs with targeted integration of interleukin24 into rDNA loci

Abstract: Induced pluripotent stem cells (iPSCs) are a promising source of mesenchymal stem cells (MSCs) for clinical applications. In this study, we transformed human iPSCs using a non-viral vector carrying the IL24 transgene pHrn-IL24. PCR and southern blotting confirmed IL24 integration into the rDNA loci in four of 68 iPSC clones. We then differentiated a high expressing IL24-iPSC clone into MSCs (IL24-iMSCs) that showed higher expression of IL24 in culture supernatants and in cell lysates than control iMSCs. IL24-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 55 publications
0
34
0
Order By: Relevance
“…Mesenchymal stem cells (MSCs) including the hWJSCs derived from within the umbilical cord have been used as anticancer agents either naïve or engineered against various human cancers (2022). The hWJSCs have many advantages compared to other currently available MSCs such as painless harvest as they are derived from umbilical cord which are usually discarded at birth, relatively young when derived, highly proliferative, have long telomeres and widely multipotent (14).…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) including the hWJSCs derived from within the umbilical cord have been used as anticancer agents either naïve or engineered against various human cancers (2022). The hWJSCs have many advantages compared to other currently available MSCs such as painless harvest as they are derived from umbilical cord which are usually discarded at birth, relatively young when derived, highly proliferative, have long telomeres and widely multipotent (14).…”
Section: Discussionmentioning
confidence: 99%
“…These properties indicate that the rDNA locus may be an ideal safe locus for transgene integration [ 7 , 8 ]. In our previous studies, exogenous genes have been targeted to the rDNA region and stably expressed in various cell lines by non-viral plasmids, including immortal adult cells and stem cells [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regards, several studies reported that hWJSCs have an appropriate anticancer activity through various mechanisms [5,9]. This stem cells are easily derived from umbilical cord and suggested as an anticancer agent [16,17]. The hWJSCs presents several advantages as compared to other stem cells, and are derived from human umbilical cord which are discarded at birth.…”
Section: Discussionmentioning
confidence: 99%